Identifikasi Gejala Dan Faktor Risiko Kejadian Penyakit Mirip African Swine Fever Di Kota Kupang - Remigius Juliano No Potu; Annytha I.R Detha; Larry W.R Toha (Jurnal Veteriner Nusantara, 2023)
Pigs as livestock are playing role as providers and contributors of animal protein sources other than poultry and cattle. African swine fever (ASF) is a double-stranded DNA virus, in the family Asfarviridae and genus Asfivirus. ASF is an infectious disease in pigs with a mortality rate of 100%. The purpose of this study was to identify symptoms and risk factors that were similar to African swine fever (ASF) in Kupang City and to examine the dominant clinical symptoms of African swine fever (ASF)-like disease in Kupang City. Data were obtained from filling out questionnaires by 250 respondents as pig farmers. Primary data were processed and analyzed using SPSS and then presented in the form of graphs and tables. The results showed that ASF-like disease had general and specific clinical symptoms. However, the incidence of abortion in pregnant sows is rarely found, this is based on the number of farmers whose sows experienced abortions as much as 41.6%. Risk factors that can cause ASF-like diseases in Kupang City, namely the lack of public knowledge about livestock systems and management, poor application of biosecurity, feeding contaminated with ASF virus (swill feeding), frequent cross-breeding of livestock. In addition, there also risk factors for ASF-like diseases originating from human activities (anthropogenic) such as visiting.